Uptake of Climate-Smart Agriculture in West Africa: What can we learn from climate-smart villages of Ghana, Mali and Niger? - Ouédraogo, Mathieu; Partey, Samuel T.; Zougmoré, Robert B.; Nyuor, Anslem Bawayelaazaa; Zakari, Seydou; Traoré, Kalifa B. (2018)
In West Africa, the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) has been working since 2011 with various local partners to develop Climate-Smart villages (CSV) through participatory action research (PAR) at pilot sites in Burkina Faso, Ghana, Mali, Niger and Senegal. Various CSA technologies and practices have been identified and tested in these CSVs. Some of these technologies and practices include: improved varieties of crops, soil and water conservation techniques (e.g. Zaï, half-moon, tie ridging), tree planting (agroforestry), farmer managed natural regeneration (FMNR), integrated soil fertility management techniques (micro-dosing, use of organic manure /compost, crop association), etc. In West Africa, adoption of agricultural innovations are thought to be constrained by several socioeconomic, institutional, infrastructural, biophysical and political factors. Therefore from the perspective of scaling up proven CSA technologies and practices at the CSVs, it is crucial to understand the determinants of their adoption.